2022
DOI: 10.1109/jphotov.2021.3135258
|View full text |Cite
|
Sign up to set email alerts
|

PV Module Energy Rating Standard IEC 61853-3 Intercomparison and Best Practice Guidelines for Implementation and Validation

Abstract: The IEC 61853 standard series aims to provide a standardized measure for PV module energy rating, namely the Climate Specific Energy Rating (CSER). For this purpose, it defines procedures for the experimental determination of input data and algorithms for calculating the CSER. However, some steps leave room for interpretation regarding the specific implementation. To analyze the impact of these ambiguities, the comparability of results and the clarity of the algorithm for calculating the CSER in part 3 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…For the ER calculation, this study adopts the methodology presented in Ref. [17], which has been validated through a Round Robin study to reduce ambiguities in certain steps of the standard procedure. The implementation tools from Ref.…”
Section: Methodsmentioning
confidence: 99%
“…For the ER calculation, this study adopts the methodology presented in Ref. [17], which has been validated through a Round Robin study to reduce ambiguities in certain steps of the standard procedure. The implementation tools from Ref.…”
Section: Methodsmentioning
confidence: 99%
“…To be consistent and thus comparable with monofacial IEC 61853-3 standard, we keep the four main calculation steps. We follow the best practice guidelines 19 established for the front side, except where the bifacial nature of the module requires us to make the adjustments discussed in the following.…”
Section: Calculation Flowmentioning
confidence: 99%
“…To analyze the differences between these definitions, we use the open source data for the monofacial c-Si "module 1" as published by Vogt et al 19 As no such data are available for bifacial modules, we assume for the purpose of calculating the bifacial energy rating that this module has rear side with the same angular loss coefficient and spectral response as the front side. This completes the PV module input data for our calculation procedure.…”
Section: Bifacial Energy Rating In Reference Climatesmentioning
confidence: 99%
“…It took five rounds of calculations—and discussions among the participants—for the nine participants' calculations to agree within 0.1%. Ultimately, Vogt et al 12 demonstrated how user‐induced variability can be reduced when modelers have clear procedures for implementing key steps of the PV model chain.…”
Section: Introductionmentioning
confidence: 99%
“…11 These modelers were required to independently obtain meteorological data for their simulations, which, for the Italian site, led to 6% differences in global horizontal irradiance (GHI), 20% differences in Gpoa, and ultimately nearly 30% differences in AC energy. And most recently, Vogt et al 12 conducted an intercomparison of energy rating calculations per IEC 61853-3 13 with nine European institutes. Energy rating differences of 14% were found in the first blind comparison round.…”
mentioning
confidence: 99%